Interactive Tourism Website Balai Pemuda Surabaya with Spherical Cameras - Yong, Raul Javier De; Budisusanto, Yanto; Hidayat, Husnul (GEOID, 2023)
Balai Pemuda Surabaya or now commonly called Surabaya square, is one of the historical buildings in the city of Surabaya. According to Bappeko Surabaya, this Balai Pemuda building began to be established in 1907 during the Dutch East Indies colonial period. The name of this building is De Simpangsche Societeit. In the Dutch colonial period, this building was used as a recreation centre for Dutch people to dance and exercise, such as bowling. In 2011, the Balai Pemuda Building experienced a fairly large fire incident in the west side building which is usually used for parties, exhibitions, art performances, and weddings. Regional revenues decreased after the fire incident. In 2013, the Surabaya city government carried out revitalization and was completed in 2015. To increase the number of tourists who will visit this tourist spot, the idea emerged to make Interactive Tourism Website Balai Pemuda Surabaya with Spherical Cameras. The results of this study were obtained via a virtual tour of Gedung Merah Putih and the surrounding area. Data from spherical cameras and non-spatial data are uploaded to the virtual tour Balai Pemuda website. The final step was to calculate the usage rate for a website that had already been built by roughly 88.5%.